Chemical speciation and phytoavailability of Cr, Ni, Zn and Cu in loess amended with attapulgite-stabilized sewage sludge. Issue 1 (1st January 2019) - Dai, Liang; Ren, Jun; Ling, Tao; Wei, Bigui; Wang, Gang
ABSTRACT: The mobility and phytotoxicity of heavy metals in the sludge produced by municipal wastewater treatment plants are key environmental factors limiting the agricultural application of sludge. To reduce the mobility and phytoavailability of Cr, Ni, Zn and Cu, the effect of attapulgite as a stabilizer on metal stabilization in sludge was investigated. Loess soil amended with attapulgite-stabilized sludge was used to grow corn under greenhouse conditions. Attapulgite was most suitable for the stabilization of these metals because it reduced the mobile fraction while increasing the contents of the residual fractions. Meanwhile, attapulgite amendment significantly reduced the DTPA-extractable Cr, Ni and Zn concentrations in the sludge and the accumulation of heavy metals in corn, which increased the dry biomass of corn. The amounts of acid-soluble, reducible and oxidizable fractions in rhizosphere soils were significantly positively correlated with the heavy metal contents in corn, in contrast to the residual metals.